The nexus between foreign direct investment and environmental sustainability in North Africa - Marwa Lazreg; Ezzeddine Zouari (Environmental Economics, 2018)
This paper provides a study of the relationship between sustainable development and foreign direct investment (FDI) from an empirical point of view in the case of the North African countries during the period from 1985 to 2005. We use the cointegration test, the FMOLS (Fully Modified Ordinary Least Squares) model and the Granger causality test to examine this relationship. According to the empirical results, we confirm the existence of a cointegration relationship between the different series studied in this paper. Based on the cointegration test we can use the error correction model. Also, to test the effect of FDI on sustainable development in the North African countries, we make an estimate by FMOLS method. We found that the foreign direct investment has a positive impact on CO2 emissions. Also, the Granger Causality test confirms the presence of a bidirectional relationship between FDI and CO2 emissions (Carbon dioxide). That is to say, the FDI can cause CO2 emissions and CO2 emissions can cause FDI based on the Granger causality.